Gravação e Atuação Musical numa Rede Web de Instrumentos Acústicos - Tiago Carvalhido Morim Casanova (2013)
Providing a Web platform for recording or performing MIDI compositions on acoustic instruments allows composers to take advantage of what the two technologies can bring to musical expression. These advantages reflect, for example, on the possibility of recording without attending the venue, on operating acoustic instruments without the need for an interpreter, or on displaying simultaneously in several places and motivate the emergence of services that offer some of these valences. Scientifically speaking, the implementation of a similar system would exploit on the study of the consequences of the potential and the limitations of these systems for musical expression and its technological solutions, while also identifying the future directions in the area of network music, concurrently at the technical and artistic level. The technological platform for this system is in continuous development. Notwithstanding, this work focus mainly on adding support for the reception of MIDI compo